Root and tuber flours to improve nutritional quality in instant noodles (Research, Society and Development, 2021)
The instant noodle (IN) consumption increased significantly among the pasta. The use of regional products may increase the economic value chain, besides the increase of final product functional properties. The aim of this work was to evaluate the partial replacement of refined wheat flour by purple sweet potato, beet and carrot in IN production. The IN were evaluated regarding the fat content (after frying and rehydration), cooking properties, instrumental texture, antioxidant capacity and glycemic index. The results showed that is possible to do the replacement the wheat flour, between the studied conditions, and achieve an IN with similar characteristics to standard sample, but with higher antioxidant capacity and low glycemic index.